Christianity and Social Work: Applying an Intersubjective Framework to Clients’ Search for the Sacred in Clinical Practice - Clairissa G. Richardson (ASTEEC, 2025)
Intersubjectivity, relating to the consciousness of two minds, begs the notion that humans can relate simply through the sharing of worlds. In the absence of theoretical principles and inquiry, intersubjectivity relies on the commonality of the human condition to propel understanding. Trials that are intrinsically human, such as sorrow, grief, anger, pain, and suffering, do not necessarily require agreement to be collectively experienced. In social work practice, there is an emphasis on human relationships as an integral vehicle in the pursuit of change. However, this ideal of co-learning rarely exists within the realm of clients’ spiritual and religious lives. Current and past clinical research suggests that there exists a unidirectional system of spiritual and religious knowledge that perpetuates a unidirectional standard of thought that cannot be challenged in the clinical relationship. Considering the influence of worldly, traditional orientations of spirituality and religion, the author argues that clients’ search for the presence of God, the sacred, is compromised and thus require critical reflection to be optimized through the Holy Spirit. In addition, current clinical research highlights cultural, faith-based challenges affecting Christian social workers presented with such clinical environments. This paper seeks to introduce an intersubjective framework for exploring the personal, social, and institutional orientations that influence clients’ search for the sacred, a purpose-filled identity that inspires faith in God. Existential and humanistic theory are incorporated to aid in marrying this seeking of the sacred, and its attendance to self-disclosure and relationship in the pursuit of healing others in clinical practice.